Stormwater and Urban Resilience or Impacts of Hydro Vulnerability in Rural and Urban Areas in Brazil - Rola, Sylvia Meimaridou (2016)
The Global Climate Change on water resources has led to intensification of extreme events. Scenarios for 2050 presented on the 5th IPCC report (REVI et al, 2014) to highlight the risk of worsening water shortage in regions, which currently have sensitivity to drought and excess of these areas of flooding. The direct use of rainwater can mitigate the impacts of extreme events of drought and flood. The comparative analysis of rainwater harvesting techniques in rural and urban areas allows both diagnose potential coexistence with the semiarid region, as alternatives to large more resilient cities. Deepens the issue in two case studies. The first takes place in the Brazilian semiarid region, whose recurring living with water stress problems, enabled the implementation of the Government Program P1MC - Program 1 Million Cisterns, which already has more than 500,000 built cisterns (ASA, 2014), resulting in the change of water supply to the families of the northeastern countryside. The second occurs in urban areas and discusses the potential for development of greening techniques in constructed surfaces (vegetated surfaces) capturing rain and surface waters stimulating both the use of non-noble uses, as the strategic use, the retention of a reservoir retardation, mitigating the burden on urban drainage system and collaborating with the reduction of flooding. In this context, whether in urban or rural areas, rainwater harvesting shown as an alternative inducing more resilient environments.